Competitiveness and the Equilibrium Exchange Rate in Costa Rica - Paiva, Claudio (IMF Working Papers; Working Paper ;, 2001)
This paper evaluates several indicators of external vulnerability and estimates the equilibrium real exchange rate for Costa Rica. While current indicators are mostly positive, declining market shares of domestic exports, the expected decline in foreign direct investment, and the desirability of strengthening the reserve position recommend an improvement in the current account. Costa Rica's equilibrium real exchange rate is then estimated using the CGER and the FEER methodologies. The overall conclusion is that while there are no signs of serious external vulnerability, the real exchange rate appears to be somewhat overvalued, a situation that would be best addressed through increased fiscal discipline.